Implementasi Kinerja Mengajar Guru Penjas dalam Meningkatkan Motivasi Belajar Peserta Didik (Studi Kasus di SDN Tayem Timur 05, Kecamatan Karangpucung, Kabupaten Cilacap, Jawa Tengah) - Pikiani, Zerli; Nurjaman, Rudi Mahar; Herman, Maman; Suhendra, Dede Iman (Jurnal Keolahragaan, 2025)
This study was driven by the low learning motivation of students, which is presumed to be associated with the less optimal teaching performance of Physical Education (PE) teachers at SD Negeri Tayem Timur 05. The aim of this research is to describe the implementation of PE teachers’ teaching performance in enhancing students’ learning motivation, reviewed from the aspects of lesson planning, instructional implementation, as well as assessment and evaluation. The research applies a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation, involving informants such as the school supervisor, principal, PE teacher, Islamic education teacher, and sixth-grade classroom teacher. The findings reveal that: (1) lesson planning by PE teachers has been aligned with curriculum standards; (2) teaching activities are carried out systematically, starting from the opening to the closing stage; and (3) assessment and evaluation are organized and conducted effectively, thereby contributing positively to the improvement of students’ learning motivation.